Answer:
For [tex]x^x > 500,000[/tex] [tex]x=7[/tex]
For [tex]x^{(-x)} > 500,000[/tex] [tex]x=-7[/tex]
Step-by-step explanation:
We need to find the smallest positive whole number that satisfies the inequality:
[tex]x^x > 500,000[/tex]
We tested with x = 6
[tex]6^6=46,656[/tex]
[tex]46,656 > 500,000[/tex]
Inequality is not met because [tex]46,656 < 500,000[/tex]
We test with the following integer x = 7
[tex]7^7=823,543[/tex]
[tex]823,543 > 500,000[/tex]
Then the smallest positive integer that will make [tex]x^x > 500,000[/tex] is 7
Inequality is met.
In the same way the largest negative integer that will make [tex]x^{(-x)} >500000[/tex] is [tex]x=-7[/tex] Beacuse [tex]7^{-(-7)}=823,543[/tex]
Answer:
Smallest positive integer value for [tex]x^x>5000[/tex] is,
x = 7,
Largest negative integer value for [tex] x^{-x} >500000[/tex] is,
x = -8
Step-by-step explanation:
If [tex]x^x>500000[/tex]
∵ If x is a positive integer then the possible values of x = 1, 2, 3, 4, 5, 6, 7.....
Case 1 : If x < 7,
[tex]x^x < 500000[/tex]
Case 2 : If x ≥ 7,
[tex]x^x > 500000[/tex]
Hence, smallest positive integer value of x is 7.
Now, if [tex]x^{-x}>500000[/tex]
∵ If x is negative integer then the possible value of x = -1, -2, -3, -4,.....
Case 1 : if x is odd negative integer,
[tex]x^{-x} < 50000[/tex]
eg : -1, -3, -5, -7,...
Case 2 : If x is even negative integer then there are further two cases,
(i) x is more than or equal to -6,
[tex]x^{-x} < 500000[/tex]
eg x = -6, -4, -2,
(ii) x is less than -8,
[tex]x^{-x} > 50000[/tex]
eg : x = -10, -12, -14,...
Hence, the largest negative integer value that will make [tex]x^{-x}> 500000[/tex] is x = -8.
Which represents a perfect cube?
8.8.8
8+8+8
9.9.9.9
9+9+9+9+9
Answer:
8.8.8.
Step-by-step explanation:
8.8.8 = 8^3 = 512 Perfect cube.
8+8+8 =24
9.9.9.9 = 6561
9+9+9+9+9 = 45.
None of the others are perfect cubes.
Answer:A 8.8.8
Step-by-step explanation:i did the quiz
What is the greatest common factor of 8x and 40y
Answer:
The GCF of both the terms is 8....
Step-by-step explanation:
Given:
What is the greatest common factor of 8x and 40y.
The GCF of 8x and 40y is 8.
We will use the method of prime factorization to find the greatest common factor.
The prime factorization of 8x is:
8x = 2*2*2*x
The prime factorization of 40y is:
40y = 2*2*2*5*y
Therefore the common factors in both the terms are 2*2*2 which becomes 8
Thus the GCF of both the terms is 8....
Answer:
8
Step-by-step explanation:
7.
chef has 50 pounds of strip Zebra. The trim loss on the strip zebra is
40% and the cooking loss is 60% of the trimmed weight. How many
pounds of trimmed, cooked strip zebra will the chef have left to serve to
his customers?
Answer:
12 pounds
Step-by-step explanation:
After trimming:
50 − 0.40 (50) = 0.60 (50) = 30
After cooking:
30 − 0.60 (30) = 0.40 (30) = 12
What is the solution to 2x-8 <12?
Answer:
[tex]x < 10[/tex]
Step-by-step explanation:
[tex]2x - 8 < 12 \\ 2x - 8 + 8 < 12 + 8 \\( 2x < 20) \div 2 = x < 10[/tex]
x<10 is the solution to the inequality 2x - 8 < 12
To solve the inequality 2x - 8 < 12, you can follow these steps:
Add 8 to both sides of the inequality:
2x - 8 + 8 < 12 + 8
This simplifies to:
2x < 20
Divide both sides of the inequality by 2:
(2x)/2 < 20/2
This simplifies to:
x < 10
Therefore, the solution to the inequality 2x - 8 < 12 is x < 10.
Learn more about inequalities here:
https://brainly.com/question/30231190
#SPJ6
Which properties of equality are used to solve the following (in no particular order)?
3(x + 12) - 2 = 50
Addition Property of Equality
Subtraction Property of Equality
Division Property of Equality
Combine Like Terms
Distributive Property
All except combine like terms. Since you only have 1 variable.
Hope this helps.
r3t40
in 135 space shuttle missions, there were two failures. Based on these data, what's the probability of a successful mission?
Answer:
98.518 repeating prercent
Step-by-step explanation:
2 out of 135 can also be written as 2/135
2 divided by 135 is 0.014814814814
that number is the percentage of failures
100% in decimal form is 1.00
1.00 subtracted by the percentage of failures is the percentage of successes
which is .98518518518, 518 repeating move the decimal over 2 and you got the percentage 98.518 repeating
Use the graph of f(x) to evaluate the following:
The average rate of change of f from x=0 to x=4 is_____.
Give your answer as an integer or reduced fraction
Answer:
-5/4
Step-by-step explanation:
The average rate of change of f from x=0 to x=4 is_____.
This means we are being asked to evaluate [tex]\frac{f(4)-f(0)}{4-0}[/tex].
To do this we will need to find f(0) and f(4).
f(0) means what y-coordinate corresponds to x=0 on the curve. Find x=0, the curve is above there, go straight up and see y=5 there. This means f(0)=5.
f(4) means what y-coordinate corresponds to x=4 on the curve. Find x=4, then curve is above there, go straight up and see y=0 there. This means f(4)=0.
So we have:
[tex]\frac{f(4)-f(0)}{4-0}=\frac{0-5}{4-0}=\frac{-5}{4}[/tex].
Which one of the following equations could describe the graph above?
Answer: A. y=(1/2)^x+6
Step-by-step explanation: If this is the graph you’re talking about-
When “a” is less than one, the graph increases exponentially to the left. The smaller the value of a, the steeper the slope of the line.
There is a vertical shift up 6 as well
What is 7(x+6)=3(x+9)
Answer:
x= -3.75
Step-by-step explanation:
Answer:
x = -15/4
Step-by-step explanation:
7(x+6)=3(x+9)
Distribute
7x+42 = 3x+27
Subtract 3x from each side
7x-3x+42 = 3x-3x+27
4x +42 = 27
Subtract 42 from each side
4x+42-42 = 27-42
4x =-15
Divide each side by 4
4x/4 =-15/4
x = -15/4
Which expression is equivalent to log3(x + 4)?
log3 - log(x + 4)
log12 + logx
log3 + log(x + 4)
log 3/log(x+4)
Answer:
log[3(x+4)] is equal to log(3) + log(x + 4), which corresponds to choice number three.
Step-by-step explanation:
By the logarithm product rule, for two nonzero numbers [tex]a[/tex] and [tex]b[/tex],
[tex]\log{(a \cdot b)} = \log{(a)} + \log{(b)}[/tex].
Keep in mind that a logarithm can be split into two only if the logarithm contains the product or quotient of two numbers.
For example, [tex]3(x + 4)[/tex] is the number in the logarithm [tex]\log{[3(x + 4)]}[/tex]. Since [tex]3(x + 4)[/tex] is a product of the two numbers [tex]3[/tex] and [tex](x + 4)[/tex], the logarithm [tex]\log{[3(x + 4)]}[/tex] can be split into two. By the logarithm product rule,
[tex]\log{[3(x + 4)]} = \log{(3)} + \log{(x + 4)}[/tex].
However, [tex]\log{(x + 4)}[/tex] cannot be split into two since the number inside of it is a sum rather than a product. Hence choice number three is the answer to this question.
Answer:
c
Step-by-step explanation:
16. The dimensions of a window are 3x + 10 and 2x + 6. What is the area of the window?
Answer:
Answer in factored form (3x+10)(2x+6)
Answer in standard form 6x^2+38x+60 ( I bet you they want this answer)
Step-by-step explanation:
The assumption is this is a rectangle.
If you have the dimensions of a rectangle are L and W, then the area is equal to L times W.
So here we just need to multiply (3x+10) and (2x+6).
The answer in factored form is (3x+10)(2x+6).
I bet you they want the answer in standard form.
So let's use foil.
First: 3x(2x)=6x^2
Outer: 3x(6)=18x
Inner: 10(2x)=20x
Last: 10(6)=60
----------------Add up!
6x^2+38x+60
The area of the window is 3x² + 19x + 30
The dimension of the window are 3x + 10 and 2x + 6.
The area of the window can be calculated as follows;
area = lw
Therefore,
area = (3x + 10)(2x + 6)
area = 6x² + 18x + 20x + 60
area = 6x² + 38x + 60
area = 3x² + 19x + 30
read more: https://brainly.com/question/3518080?referrer=searchResults
[tex] - 3 + 5i \div - 3 - 4i[/tex]
Answer:
[tex]\frac{-11}{25}+\frac{-27}{25}i[/tex] given you are asked to simplify
[tex]\frac{-3+5i}{-3-4i}[/tex]
Step-by-step explanation:
You have to multiply the numerator and denominator by the denominator's conjugate.
The conjugate of a+bi is a-bi.
When you multiply conjugates, you just have to multiply first and last.
(a+bi)(a-bi)
a^2-abi+abi-b^2i^2
a^2+0 -b^2(-1)
a^2+-b^2(-1)
a^2+b^2
See no need to use the whole foil method; the middle terms cancel.
So we are multiplying top and bottom of your fraction by (-3+4i):
[tex]\frac{-3+5i}{-3-4i} \cdot \frac{-3+4i}{-3+4i}=\frac{(-3+5i)(-3-4i)}{(-3-4i)(-3+4i)}[/tex]
So you will have to use the complete foil method for the numerator. Let's do that:
(-3+5i)(-3+4i)
First: (-3)(-3)=9
Outer:: (-3)(4i)=-12i
Inner: (5i)(-3)=-15i
Last: (5i)(4i)=20i^2=20(-1)=-20
--------------------------------------------Combine like terms:
9-20-12i-15i
Simplify:
-11-27i
Now the bottom (-3-4i)(-3+4i):
F(OI)L (we are skipping OI)
First:-3(-3)=9
Last: -4i(4i)=-16i^2=-16(-1)=16
---------------------------------------------Combine like terms:
9+16=25
So our answer is [tex]\frac{-11-27i}{25}{/tex] unless you want to seprate the fraction too:
[tex]\frac{-11}{25}+\frac{-27}{25}i[/tex]
Solve this inequality: 36 - 7 < 32
You already did. That is a true statement.
32 > 29 [and vice versa]
I am joyous to assist you anytime.
The inequality 29 < 32 is true.
After calculating 36 - 7 which equals 29, we compare this result to 32. The inequality 29 < 32 holds true, so the original inequality 36 - 7 < 32 is correct.
The student has asked to solve the inequality 36 - 7 < 32. To solve this inequality, we need to perform the subtraction on the left side of the inequality first.
When we calculate 36 - 7, we get 29. Now we can compare this result to 32 to determine if the inequality holds true.
Since we are dealing with an inequality, we know that if a value a is less than a value b, then a is indeed smaller in quantity or value compared to b. Here, 29 is indeed less than 32. Therefore, the inequality 29 < 32 is true.
What is the length of the hypotenuse in the right triangle shown below?
Answer:
C. 6√2.
Step-by-step explanation:
Since this is a right angled isosceles triangle bot legs are 6 units long
So h^2 = 6^2 + 6^2 = 72
h = √72 = 6√2.
Answer:
The correct option is C) 6√2.
Step-by-step explanation:
Consider the provided triangle.
The provided triangle is a right angle triangle, in which two angles are 45° and one is 90°.
As both angles are equal there opposite side must be equal.
Thus, the leg of another side must be 6.
Now find the hypotenuse by using Pythagorean theorem:
[tex]a^2+b^2=c^2[/tex]
Substitute a = 6 and b = 6 in [tex]a^2+b^2=c^2[/tex].
[tex](6)^2+(6)^2=(c)^2[/tex]
[tex]36 + 36=(c)^2[/tex]
[tex]72=(c)^2[/tex]
[tex]6\sqrt{2}=c[/tex]
Hence, the length of the hypotenuse in the right triangle is 6√2.
Therefore, the correct option is C) 6√2.
The digits of a two-digit number sum to 8. When the digits are reversed, the resulting number is 18 less than the original
number. What is the original number?
Answer:
It's 53.
Step-by-step explanation:
Let the number be xy so the digits are x and y, so:
x + y = 8...........(1)
Reversing the 2 digits we have the number 10y + x and this equals
10x + y - 18 so we have the equation:-
10x + y - 18 = 10y + x
9x - 9y = 18
x - y = 2...........(2) Adding equations (1) and (2) we have:
2x = 10
x = 5
and y = 8 - 5 = 3.
So the original number is 53.
We can check this as follows
Original number is 53 so the reverse is 35 .
53 - 35 = 18 which checks out.
Need The Answer Plz And Thank You!! I’m Failing
Angle BCA
Step-by-step explanation:
You can see this due to the angle having the name amount of congruent angle marks.
Let f(x) = 4x - 7 and g(x) = 2x - 3. Find (fog)(4).
Answer:
13
Step-by-step explanation:
(f∘g)(4) is another way of writing f(g(4)).
First, find g(4).
g(x) = 2x − 3
g(4) = 2(4) − 3
g(4) = 5
Now substitute into f(x).
f(x) = 4x − 7
f(g(4)) = 4g(4) − 7
f(g(4)) = 4(5) − 7
f(g(4)) = 13
[tex](f\circ g)(x)=4(2x-3)-7=8x-12-7=8x-19\\\\(f\circ g)(4)=8\cdot4-19=13[/tex]
When solving -1/5 (x − 25) = 7, what is the correct sequence of operations?
A:Multiply each side by negative one over five , add 25 to each side
B:Multiply each side by 5, subtract 25 from each side
C:Multiply each side by negative one over five , subtract 25 from each side
D;Multiply each side by −5, add 25 to each side
Answer:
It is C. Multiply each side by negative one over five , subtract 25 from each side.
Hope this helped you! :3
Answer:
D;Multiply each side by −5, add 25 to each side
Step-by-step explanation:
-1/5 (x − 25) = 7
To solve this equation, we will first multiply both-side of the equation by -5
-5 × -1/5(x-25) =7 × 5
(At the left-hand side of this equation, the 5 we multiplied will cancel the 5 at the denominator, leaving us with just '1' since negative multiply by negative is positive), Hence our equation becomes;
(x - 25) = 35
x - 25 = 35
Then the next thing to do is to add 25 to both-side of the equation in other to get the value of your x
x -25 + 25 = 35 + 25
x=60
Therefore, option D is the correct sequence of operation to follow to enable you solve the equation.
Three terms of an arithmetic sequence are shown below. Which recursive formula defines the sequence? f(1) = 6, f(4) = 12, f(7) = 18 f (n + 1) = f(n) + 6 f (n + 1) = 2f(n) f (n + 1) = f(n) + 2 f (n + 1) = 1.5f(n)
Answer:
f(n + 1) = f(n) + 2
Step-by-step explanation:
A recursive formula gives any term in the sequence from the previous term.
the n th term of an arithmetic sequence is
f(n) = f(1) + (n - 1)d ← d is the common difference
Given
f(1) = 6 and
f(4) = 12, then
f(1) + 3d = 12, that is
6 + 3d = 12 ( subtract 6 from both sides )
3d = 6 ( divide both sides by 3 )
d = 2
To obtain a term in the sequence add 2 to the previous term, hence
f(n + 1) = f(n) + 2 ← recursive formula
Answer:
c
Step-by-step explanation:
its c
HELPPPP WILL NAME BRAINIEST
Answer:
Triangle APB is an isosceles triangle ⇒ 3rd answer
Step-by-step explanation:
* Lets explain the how to solve the problem
- ABCD is a square
∴ AB = BC = CD = AD
∴ m∠A = m∠∠B = m∠C = m∠D = 90°
- DPC is equilateral triangle
∴ DP = PC = DC
∴ m∠DPC = m∠PCD = m∠CDP = 60°
- In the Δs APD , BPC
∵ AD = BC ⇒ sides of the square
∵ PD = PC ⇒ sides of equilateral triangle
∵ m∠ADB = m∠BCP = 30° (90° - 60° = 30) ⇒ including angles
∴ Δs APD , BPC are congregant ⇒ SAS
- From congruent
∴ AP = BP
∴ Triangle APB is an isosceles triangle
Two tins are geometrically similar. If the ratio of their volume is 27:64 find the ratio of their curved surface area.
Answer:
9 : 16
Step-by-step explanation:
Given 2 similar figures with linear ratio = a : b, then
area ratio = a² : b² and
volume ratio = a³ : b³
Here the volume ratio = 27 : 64, hence
linear ratio = [tex]\sqrt[3]{27}[/tex] : [tex]\sqrt[3]{64}[/tex] = 3 : 4
Hence area ratio = 3² : 4² = 9 : 16
4x – 9y = 7
–2x + 3y = 4
What number would you multiply the second equation by in order to eliminate the x-terms when adding to the first equation?
Answer:
By 2.
Step-by-step explanation:
You need to eliminated the x-terms, so the first step is to focus only in those terms.
So yo have 4x and -2x, since you are thinking in eliminate then you have this equation>
[tex]4-2*K=0[/tex]
Note that we dont put the x variable, since we are studying its coefficients in the equations system.
Solving for K, Gives us that K=2
So.
Multiplying the second equation by 2 results in
[tex]-4x+6y=8[/tex]
When you put them together, it gives you the following
[tex]4x-9y -4x+6y- 7+8[/tex]
and the final equation is
[tex]-3y=15\\[/tex]
giving you the answer for y, that is [tex]y=-5[/tex]
Answer: 2 and 3.
Step-by-step explanation:
Rowena walks 3 kilometers a day. How many meters does she walk in three days?
[tex]\huge{\boxed{\text{9,000 meters}}}[/tex]
There are 1,000 meters in each kilometer, so multiply to find the daily number of meters. [tex]3*1000=3000[/tex]
Multiply this by 3 to find the number of meters Rowena walks in three days. [tex]3000*3=\boxed{9000}[/tex]
Find the value of x.
A. 1.1
B. 6.6
C. 8.8
D. 5.5
Answer:
B. 6.6Step-by-step explanation:
AC is a midsegment of the trapezoid DFBE.
The formula of a midsegment of trapezoid is:
[tex]m=\dfrac{a+b}{2}[/tex]
a, b - bases of a triangle
We have
a = x, b = 4.4, m = 5.5
Substitute:
[tex]5.5=\dfrac{x+4.4}{2}[/tex] multiply both sides by 2
[tex]11=x+4.4[/tex] subtract 4.4 from both sides
[tex]6.6=x\to x=6.6[/tex]
Events A and B are disjointed.
P(A) = 4/11 ; P(B) = 3/11.
Find P(A or B).
*Answer Options*
7/11
4/11
3/11
8/11
Answer:
7/11
Step-by-step explanation:
Two events are disjoint events if they cannot occur at the same time. It is given that A and B are disjointed events, so A and B cannot occur at the same time i.e. the intersection of two disjoint events will be 0.
For two disjoint events A and B:
P(A or B) = P(A) + P(B)
P(A) is given to be 4/11 and P(B) is given to be 3/11. Using these values in the equation, we get:
P(A or B) = [tex]\frac{4}{11}+\frac{3}{11} = \frac{3+4}{11}=\frac{7}{11}[/tex]
A group of students and workers entering a metro station
were asked whether they were riding the bus or the
subway. The two-way table shows their answers.
Types of Transportation
Bus
Subway
Students
Workers
Total
166
27 + 42 + 21 + 76 = 166
In circle O, AD and BE are diameters. What is m? 106° 132° 138° 164°
Answer:
It is 132 just took it
Step-by-step explanation:
Each of the pairs of opposite angles made by two intersecting lines is called a vertical angle. The measure of ∠AOE is 132°. The correct option is B.
What are vertical angles?Each of the pairs of opposite angles made by two intersecting lines is called a vertical angle.
In circle O, AD and BE are diameters. Also, the measure of ∠EOD and ∠AOB will be equal because the two angles are vertically opposite angles. Therefore,
∠EOD = ∠AOB = 3x
As it is given that the measure of ∠AOC is 90°. Therefore, we can write,
∠AOC = ∠AOB + ∠BOC
90 = 3x + 0.5x + 34
56 = 3.5x
x = 16
Now, the measure of ∠EOD will be,
∠EOD = 3x
∠EOD = 3(16°)
∠EOD = 48°
Further, we can write,
∠AOD = ∠AOE + ∠EOD
180° = ∠AOE + 48°
∠AOE = 132°
The complete question is mentioned in the below image.
Learn more about Vertical Angles:
https://brainly.com/question/24460838
#SPJ2
What is the midpoint of the segment shown below?
Answer:
A
Step-by-step explanation:
Calculate the midpoint using the midpoint formula
[ 0.5(x₁ + x₂ ), 0.5(y₁ + y₂ ) ]
with (x₁, y₁ ) = (- 1, 5) and (x₂, y₂ ) = (5, 5)
midpoint = [ 0.5(- 1 + 5), 0.5(5 + 5) ]
= [ 0.5(4), 0.5(10) ] = (2, 5 ) → A
Answer:
The answer would be A 2,5
Step-by-step explanation:
If Sn=n^2+3 then t10=?
Answer:
T10= -21
Step-by-step explanation:
If Sn=n^2+3 then t10=?
Sn= n²+5
put n=1, 2
S1= T1 = (1)²+5
=1+5 =6
S2= n²+5
S2=(2)²+5
S2=4+5
S2=9
T2 = S2 - S1
T2 = 9-6
T2=3
T10 = a+(n-1)d
where a = 6, d = -3, n=10
T10= 6+(10-1)*-3
T10=6+(9)*-3
T10=6+(-27)
T10=6-27
T10= -21
Therefore T10= -21 ....
-8(5x+5)+9x(10x+9)=20
[tex]-8(5x+5)+9x(10x+9)=20\\-40x-40+90x^2+81x-20=0\\90x^2+41x-60=0\\\\\Delta=41^2-4\cdot90\cdot(-60)=1681+21600=23281\\\\x=\dfrac{-41\pm \sqrt{23281}}{2\cdot90}=\dfrac{-41\pm \sqrt{23281}}{180}[/tex]